Desenvolvimento moral e uso de redes sociais de relacionamento na internet: uma relação possível? - Aline Cristiane Lemos Ferreira (2007)
This study aimed to examine, from the perspective socio-cultural history, the influence of social networks of relationships on the Internet in moral development of adolescents. We studied 157 high school students of a public institution of Belo Horizonte, aged 14 and 19 years. From aquestionnaire was initially a survey of the user profile of adolescent social networks on the Internet. Then, using the DIT and G-36, focuses on the moral development and intelligence of the sample trying to identify the correlations found in literature. Subsequently, using moral dilemmasdesigned specifically for the study, it was, through content analysis, identifying the moral position of the subjects in a situation of virtual interaction. The results point to the need to consider the contexts of social interaction as important for the moral development of adolescents,is contrasting the prevalent perception in the prevailing literature on the subject, the cognitivedevelopmental perspective.